2010
DOI: 10.1103/physreva.82.059902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Extended Thomas-Fermi density functional for the unitary Fermi gas [Phys. Rev. A78, 053626 (2008)]

Abstract: Recently M. Manzoni and N. Manini, who reanalyzed [1] the determination of parameters ξ and λ of the extended Thomas-Fermi density functional on the basis of Monte Carlo data [2], pointed out a possible error in our previous deter-mination of these parameters. By repeating the calculations we indeed find that the best-fit values are slightly different: ξ = 0.468 and λ = 0.086. This modification does not change any of the physical conclusions of our paper.[1] M. Manzoni, B.Sc. Thesis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(136 citation statements)
references
References 1 publication
6
130
0
Order By: Relevance
“…They find c 1 ≃ − √ 2/(30π 2 ξ 3/2 ) and c 2 ≃ 0, corresponding to γ = 1/(30mµ). Other estimates of γ can be found in [28][29][30].…”
Section: Elementary Excitationsmentioning
confidence: 99%
“…They find c 1 ≃ − √ 2/(30π 2 ξ 3/2 ) and c 2 ≃ 0, corresponding to γ = 1/(30mµ). Other estimates of γ can be found in [28][29][30].…”
Section: Elementary Excitationsmentioning
confidence: 99%
“…By using a Madelung transformation, equations (1) and (2) can equivalently be written in the form of a time-dependent nonlinear Schrödinger equation (NLSE) [14] involving the complex order parameter Ψ(r, t) = n(r, t) e iθ(r,t) :…”
Section: Methods and Calculationsmentioning
confidence: 99%
“…The above equations describe accurately various static and dynamical properties of the UFG. The term multiplied by λ is found to be crucial to accurately describe surface effects, in particular in systems with a small number of atoms, where the Thomas-Fermi (local density) approximation fails [14]. We have shown that when fast dynamical processes occur and/or when shock waves come into play such term is necessary also in the large N limit [18], where results in quantitative agreement with experiments of real-time collision of strongly interacting Fermi gas clouds at unitarity [19] can be obtained [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations